Reparations for damages emerging and derived from not recognizing a child born out of wedlock - Meza Soto, Lialka Nataly (2016)
Regarding the violation of parental duties, one that deserves special attention is that of children born from extramarital affairs since they suffer from the disdain of not being recognized voluntarily by their parents, until their parentage is declared legally. Therefore, considering the real violation of the right to personal identity, the right to know one’s own biological origins, and the right to enjoy the appropriate legal familial situation as a child, this paper examines and determines the repairable damages caused by such denial of voluntary recognition based on the scholars and foreign jurisprudence. In this context, the denial of parent-child relationship, whether due to gross or ordinary negligence, is the grounds for such damages.